Creating Value Through ESG: Strategies and Solutions - Feng Shidi (SHS Web of Conferences, 2025)
This study explores how companies can cope with challenges in the process of implementing ESG strategies. By analyzing the solutions of other companies in the same industry and combining the specific circumstances of the companies, this study deeply explores the obstacles faced by companies in the process of ESG strategy formulation and implementation and provides practical solutions. The results show that companies can mitigate regional policy restrictions and their negative impacts by advocating a more favorable policy and regulatory environment, continuous innovation and technological development can ease competitive pressure, the risks of investing in emerging technologies can be reduced through comprehensive risk assessments, actively communicating with local governments and adjusting strategies according to local conditions can overcome infrastructure limitations, and effective management of environmental and social factors requires active collaboration with stakeholders. The implication of this study is to provide companies with feasible strategies for coping with the complexity of ESG, ultimately promoting more sustainable and responsible business practices.